A low profile dual band MIMO antenna for LTE/Bluetooth/Wi-Fi/WLAN applications. Issue 9 (12th June 2020) - Tiwari, Rakesh N.; Singh, Prabhakar; Kanaujia, Binod Kumar; Kumar, Sachin; Gupta, Surendra Kumar
ABSTRACT: In the present endeavor, a CPW-fed dome-shaped monopole radiating elements with 2 × 2 MIMO configuration is presented. The dual-band response of the antenna is obtained by embedding a pair of comb-shaped slots in the ground plane. The measured dual frequency bands of 2.11–4.19 GHz (lower) and 4.98–6.81 GHz (upper) effectively cover LTE, Wi-Fi/WLAN, Bluetooth, and Wi-MAX applications. A T-shaped stub is integrated with the ground plane to obtain high isolation (>21 dB). The measured antenna gain varies in the range of 2.75–4.19 dBi and its radiation efficiency is found greater than 70% in both the resonating bands. The overall size of the proposed antenna is 20 × 34 × 1.6 mm 3 . The antenna is fabricated and measured results are validated with the results obtained by CST Microwave Studio. Finally, various diversity parameters are evaluated for the antenna and the results are satisfactory for MIMO applications.